2020
DOI: 10.1002/cjp2.165
|View full text |Cite
|
Sign up to set email alerts
|

Endometrial stromal sarcomas with BCOR‐rearrangement harbor MDM2 amplifications

Abstract: Recently a novel subtype of endometrial stromal sarcoma (ESS) defined by recurrent genomic alterations involving BCOR has been described (HGESS‐BCOR). We identified a case of HGESS‐BCOR with a ZC3H7B‐BCOR gene fusion, which harbored an amplification of the MDM2 locus. This index case prompted us to investigate MDM2 amplification in four additional cases of HGESS‐BCOR. Tumors were analyzed for MDM2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 21 publications
2
39
0
Order By: Relevance
“…Furthermore, some but not all ZC3H7B/BCOR positive HG‐ESS are characterized by the presence of also the reciprocal transcript 51,52,56 whose role in tumorigenesis and/or progression is still unknown. Additionally, a new BCOR ‐rearranged HG‐ESS was recently reported by Kommoss et al 69 in which RNAseq identified a fusion between BCOR and LPP . The genic event behind the transcript resulted in overexpression of the C‐terminal, truncated BCOR protein but without generation of the chimera, that is, no coding part of LPP was involved.…”
Section: Chromosomal Aberrations and Their Molecular Productsmentioning
confidence: 83%
See 2 more Smart Citations
“…Furthermore, some but not all ZC3H7B/BCOR positive HG‐ESS are characterized by the presence of also the reciprocal transcript 51,52,56 whose role in tumorigenesis and/or progression is still unknown. Additionally, a new BCOR ‐rearranged HG‐ESS was recently reported by Kommoss et al 69 in which RNAseq identified a fusion between BCOR and LPP . The genic event behind the transcript resulted in overexpression of the C‐terminal, truncated BCOR protein but without generation of the chimera, that is, no coding part of LPP was involved.…”
Section: Chromosomal Aberrations and Their Molecular Productsmentioning
confidence: 83%
“…The data obtained highlighted that the LG‐ESS pattern differed from that of HG‐ESS, and that, within the latter, distinct subgrouping of YWHAE ‐ and BCOR ‐rearranged tumors was possible 91 . The copy number‐profile was investigated by the same group in a series of uterine tumors that included LG‐ESS, HG‐ESS, UTROSCT, uterine leiomyomas, and uterine leiomyosarcomas 69 . The authors identified amplification of the MDM2 gene from chromosomal band 12q15 only in BCOR ‐rearranged HG‐ESS 69 .…”
Section: Pathogenetic Consequences Of Ess‐specific Genetic Rearrangemmentioning
confidence: 98%
See 1 more Smart Citation
“…Preclinical studies have previously shown that ESS may be sensitive to HDAC inhibition, and clinical data of the phase II trial of panobinostat in advanced sarcoma are consistent [25], even if only three ESSs were enrolled in the study. Moreover, a recent paper suggested that ESS with BCOR-rearrangement harbors MDM2 amplifications [26]. Among the four HG-ESS-BCOR of our series, only one (CLB_RNA_1549) carries a MDM2-CDK4 amplification ( Figure S9).…”
Section: Discussionmentioning
confidence: 65%
“…The HGESS in the current World Health Organization classi cation is limited to tumors characterized by high-grade round cell morphology and harboring t(10;17)(q22;p13) resulting in YWHAE-NUTM2 fusion (7), A recent study have described a rare subtype of ESS with high grade features and BCOR alterations, caused by either a gene fusion between BCOR and ZC3H7B or a mutually exclusive somatic internal tandem duplication of exon 15 of BCOR (8). In the only few cases reported in the literature to date, it has been proposed that it is more aggressive as another morphological variant of HGESS (4).…”
Section: Discussionmentioning
confidence: 99%